2014
DOI: 10.1007/s10856-014-5268-3
|View full text |Cite
|
Sign up to set email alerts
|

Transparent magnesium aluminate spinel: a prospective biomaterial for esthetic orthodontic brackets

Abstract: Adult orthodontics is recently gaining popularity due to its importance in esthetics, oral and general health. However, none of the currently available alumina or zirconia based ceramic orthodontic brackets meet the esthetic demands of adult patients. Inherent hexagonal lattice structure and associated birefringence limits the visible light transmission in polycrystalline alumina and make them appear white and non transparent. Hence focus of the present study was to assess the feasibility of using magnesium al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Transparent polycrystalline ceramics like magnesium aluminate (MgAl 2 O 4 ) spinel (MAS) ceramics are of great academic and industrial interest due to their unique material properties. [ 1 , 2 , 3 ] Excellent mechanical and thermal stability combined with a low thermal expansion coefficient, high chemical and radiation resistance as well as good optical properties with transmission > 85% over a wide range from 250 nm in the ultraviolet to 6500 nm in the infrared, make MAS ceramics the material of choice for various applications ranging from infrared domes and highly resistant cover windows [ 4 , 5 , 6 ] to solid‐state lasers, [ 7 ] medical applications such as orthodontic brackets [ 8 ] and insulating materials in extremely harsh environments such as in fusion reactors. [ 9 ] Transparent MAS is especially interesting for optical applications since the ceramic features not only high transparency but also combines a high refractive index ( n 532 nm = 1.7108) with a low optical dispersion (Abbe number ≈60) enabling the fabrication of thin, optical components displaying low chromatic aberration for, e.g., ultra‐thin high‐quality camera lenses.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent polycrystalline ceramics like magnesium aluminate (MgAl 2 O 4 ) spinel (MAS) ceramics are of great academic and industrial interest due to their unique material properties. [ 1 , 2 , 3 ] Excellent mechanical and thermal stability combined with a low thermal expansion coefficient, high chemical and radiation resistance as well as good optical properties with transmission > 85% over a wide range from 250 nm in the ultraviolet to 6500 nm in the infrared, make MAS ceramics the material of choice for various applications ranging from infrared domes and highly resistant cover windows [ 4 , 5 , 6 ] to solid‐state lasers, [ 7 ] medical applications such as orthodontic brackets [ 8 ] and insulating materials in extremely harsh environments such as in fusion reactors. [ 9 ] Transparent MAS is especially interesting for optical applications since the ceramic features not only high transparency but also combines a high refractive index ( n 532 nm = 1.7108) with a low optical dispersion (Abbe number ≈60) enabling the fabrication of thin, optical components displaying low chromatic aberration for, e.g., ultra‐thin high‐quality camera lenses.…”
Section: Introductionmentioning
confidence: 99%
“…11 Since zirconia has the lowest thermal conductivity of any commercial refractory and in the meanwhile MA spinel has received a great deal of attention as a technologically important material due to its attractive properties such as high melting point, high mechanical strength at elevated temperature, high chemical inertness, and good thermal shock resistance, effect of MA addition on stabilization and densification of m-ZrO 2 was deserved to be studied. [12][13][14][15][16] Morita et al reported synthesis of nanocrystalline ZrO 2 -30 vol% MA composite by high-energy ball-milling followed by spark plasma sintering; their study showed that nanocrystallized MA has improved the strength of the composite by a factor of 2.0-2.5. 17 Holland et al prepared dense ceramic composites from Ce-TZP reinforced with 16 vol% MA; their study showed that inter/intergranular dispersion of nanoscaled magnesia spinel has led to strengthening of Ce-TZP matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Since zirconia has the lowest thermal conductivity of any commercial refractory and in the meanwhile MA spinel has received a great deal of attention as a technologically important material due to its attractive properties such as high melting point, high mechanical strength at elevated temperature, high chemical inertness, and good thermal shock resistance, effect of MA addition on stabilization and densification of m‐ZrO 2 was deserved to be studied 12‐16 …”
Section: Introductionmentioning
confidence: 99%
“…However, the fabrication of MgAl 2 O 4 ‐spinel‐based scaffold has not been reported so far. In a recent study, the authors reported the excellent biocompatibility of Magnesium Aluminate (MgAl 2 O 4 ) spinel at three levels based on the toxicological assays . The study demonstrated the overall cytotoxicity, ability to induce apoptosis and nonsusceptibility for genotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated the overall cytotoxicity, ability to induce apoptosis and nonsusceptibility for genotoxicity. In addition, the spinel has also exhibited acceptable physical and mechanical properties suggesting the formulation as an emerging bioinert ceramic material . Furthermore, spinel provides the flexibility in processing into various configurations mimicking natural bones which offers the surface topographies to promote cell substrate interaction.…”
Section: Introductionmentioning
confidence: 99%